2020
DOI: 10.1108/bfj-04-2020-0355
|View full text |Cite
|
Sign up to set email alerts
|

How do food consumption motivations and emotions affect the experiential values and well-being of foodies?

Abstract: PurposeTravellers who love to try different foods and who frequently follow up on food-related news and topics consider themselves to be “foodies”. The main aim of this research was to identify the relationships among food consumption motivations, experiential values and well-being of foodies.Design/methodology/approachA questionnaire survey was distributed to foodies from the Chinese mainland, Hong Kong and Macao in March–May 2019 who were aged 18 and above and who had visited Taiwan within the prior two year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 89 publications
4
43
1
Order By: Relevance
“…At the same time, it can also be observed that the number of students who consume a low-quality diet and an appropriate level of emotional repair was higher than those consuming a poor diet and demonstrating emotional indices in need of improvement. Largely similar results were achieved by Chang et al [ 87 ] and Jin et al [ 88 ]. These authors argued that, when some students experience unpleasant emotions, they tend to experience variations in their dietary patterns and over-feeding.…”
Section: Discussionsupporting
confidence: 86%
“…At the same time, it can also be observed that the number of students who consume a low-quality diet and an appropriate level of emotional repair was higher than those consuming a poor diet and demonstrating emotional indices in need of improvement. Largely similar results were achieved by Chang et al [ 87 ] and Jin et al [ 88 ]. These authors argued that, when some students experience unpleasant emotions, they tend to experience variations in their dietary patterns and over-feeding.…”
Section: Discussionsupporting
confidence: 86%
“…Food tourism has evolved as contemporary tourists now travel to search for and enjoy food and beverages. Emerging and growing interest in food tourism is forcing cities and regions to become more innovative in how they attract tourists (Chang et al , 2020a, b). Thus, food services are considered a core resource for destination competitiveness that offer relevant advantages to the tourism industry in terms of productivity.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of tourism, motivations can be defined as the driving forces for developing activities during a trip (Chang et al , 2020a, b). Specifically, in food tourism, understanding the motivations to visit a restaurant offering a creative experience and their effect on assessing the food experience is critical to design ad hoc marketing strategies, develop future demand and improve the restaurants' long-term performance.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, travel motivations are found to be strongly associated to tourist expectations towards trips (Fang et al, 2017). Despite these two factors being proven critical in consumer trust in the food business (Tonkin et al, 2020), predicting foodies' perceptions towards food experiential values (Chang et al, 2020) and travel intentions among tourists who have particular dietary requirements (Huang et al, 2019), in both the mainstream tourism and food literature, no study has established the relationships among travel motivations, CoE and MTEs (Fang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%